Current understanding and future directions of cruciferous vegetables and their phytochemicals to combat neurological diseases - Kakarla R.; Karuturi P.; Siakabinga Q.; Kasi Viswanath M.; Dumala N.; Guntupalli C.; Nalluri B.N.; Venkateswarlu K.; Prasanna V.S.; Gutti G.; Yadagiri G.; Gujjari L. (My University, 2025)
Neurological disorders incidences are increasing drastically due to complex pathophysiology, and the nonavailability of disease-modifying agents. Several attempts have been made to identify new potential chemicals to combat these neurological abnormalities. At present, complete abolishment of neurological diseases is not attainable except for symptomatic relief. However, dietary recommendations to help brain development or improvement have increased over the years. In recent times, cruciferous vegetables and their phytochemicals have been identified from preclinical and clinical investigations as potential neuroprotective agents. The present review highlights the beneficial effects and molecular mechanisms of phytochemicals such as indole-3-carbinol, diindolylmethane, sulforaphane, kaempferol, selenium, lutein, zeaxanthin, and vitamins of cruciferous vegetables against neurological diseases including Parkinson's disease, Alzheimer's disease, stroke, Huntington's disease, autism spectra disorders, anxiety, depression, and pain. Most of these cruciferous phytochemicals protect the brain by eliciting antioxidant, anti-inflammatory, and antiapoptotic properties. Regular dietary intake of cruciferous vegetables may benefit the prevention and treatment of neurological diseases. The present review suggests that there is a lacuna in identifying the clinical efficacy of these phytochemicals. Therefore, high-quality future studies should firmly establish the efficacy of the above-mentioned cruciferous phytochemicals in clinical settings. © 2024 John Wiley & Sons Ltd.